Analisis Peran Eco-Enzyme dalam Peningkatan Kualitas Air sebagai Cerminan Nilai Kepedulian Sosial di Masyarakat Rentan Kota Tangerang - Sharira Aulia Qumaira Ochoa; Laurencia Joceline; Prissil Presentia; Ferdy Anthonius; Christian Siregar (Yayasan Literasi Sains Indonesia, 2026)
Issues related to water quality and adequate sanitation remain crucial, including in vulnerable areas such as Tangerang City. Cipondoh District faces challenges such as low water quality and community behavior that does not yet fully reflect environmental awareness. Eco-enzyme, a liquid produced from the fermentation of organic waste, water, and molasses, has been scientifically proven to reduce water pollutants, making it a cheap, environmentally friendly, and community-applicable alternative solution. This devotion aims to analyze the role of eco-enzyme in improving water quality while examining how its implementation reflects social care values among the Cipondoh community. A descriptive qualitative approach using semi-structured interviews was employed to obtain information from six informants consisting of two eco-enzyme practitioners and four residents around Lake Cipondoh. The implementation of the activites show that public understanding of eco-enzyme remains limited, leading to uneven environmental awareness. However, eco-enzyme practices conducted by environmental communities demonstrate positive impacts on water quality and the potential restoration of aquatic ecosystems. This activities concludes that eco-enzyme serve not only as an ecological agent in improving water quality but also as an educational instrument that strengthens community awareness and social responsibility.